Organic radical imaging in plants: Focus on protein radicals - Kumar, Aditya; Prasad, Ankush; Sedlářová, Michaela; Pospíšil, Pavel (Free radical biology & medicine, 2019)
Biomolecule (lipid and protein) oxidation products formed in plant cells exposed to photooxidative stress play a crucial role in the retrograde signaling and oxidative damage. The oxidation of biomolecules initiated by reactive oxygen species is associated with formation of organic (alkyl, peroxyl and alkoxyl) radicals. Currently, there is no selective and sensitive technique available for the detection of organic radicals in plant cells. Here, based on the analogy with animal cells, immuno-spin trapping using spin trap, 5,5-dimethyl-1-pyrroline N-oxide (DMPO) was used to image organic radicals in Arabidopsis leaves exposed to high light. Using antibody raised against the DMPO nitrone adduct conjugated with the fluorescein isothiocyanate, organic radicals were imaged by confocal laser scanning microscopy. Organic radicals are formed predominantly in the chloroplasts located at the periphery of the cells and distributed uniformly throughout the grana stack. Characterization of protein radicals by standard immunological techniques using anti-DMPO antibody shows protein bands with apparent molecular weights of 32 and 34 kDa assigned to D1 and D2 proteins and two protein bands below the D1/D2 band with apparent molecular weights of 23 and 18 kDa and four protein bands above the D1/D2 band with apparent molecular weights of 41, 43, 55 and 68 kDa. In summary, imaging of organic radicals by immuno-spin trapping represents selective and sensitive technique for the detection of organic radicals that might help to clarify mechanistic aspects on the role of organic radicals in the retrograde signaling and oxidative damage in plant cell.
Keywords: Electron Spin Resonance Spectroscopy; spinové značení; Alkyl radical; lipidy; Free Radicals; Alkoxyl radical; Reactive oxygen species; cyklické N-oxidy; reaktivní formy kyslíku; proteiny; Spin Labels; peroxid vodíku; Oxidative Stress; Oxidation-Reduction; Spin Trapping; Lipids; Reactive Oxygen Species; Peroxyl radical; zvířata; Cyclic N-Oxides; Peroxides; spin trapping; elektronová paramagnetická rezonance; volné radikály; oxidace-redukce; Hydroperoxide; oxidační stres; Hydrogen Peroxide; peroxidy; Proteins; Photosystem; Animals